UPAYA DALAM MENGEMBANGKAN PENDIDIKAN BERBASIS KARAKTER DI SEKOLAH DASAR - Trisna Dinillah Harya (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
Social problems that often occur in Indonesia, especially in society environment is not something new in this modern era. The more sophisticated the development of the times makes children, teenagers and even adults difficult to control their personality that reflects the respect and discipline on the surrounding environment or against themselves will reflect the character of the poor. This will lead to juvenile delinquency, criminal acts, robbery and even free life style that can harm themselves or society. Social problems that often occur in the social environment not only has implications for adolescents but also has an impact on the students behavior at school even the students at elementary schools. Social problems, one of the effect that can cause the student less discipline. The solution for the student discipline at school is a character education. To be able to implement a character education at schools, especially at elementary school, it is necessary a good understanding of character education for the teacher, i.e. understanding of the notion of character education, values of character education, and the development of character education at elementary schools.